Exploiting directional long range secondary forces for regulating electrostatics dominated noncovalent interactions - Tiwari, Mrityunjay; Vanka, Kumar (Chemical Science, 2017)
It has been well established that long range secondary electrostatic interactions (SEIs) have a significant effect on the stability of supramolecular complexes. However, general rules for exploiting SEIs in the rational design of diverse supramolecular complexes have been difficult to obtain. In this work, we outline a quantum chemical approach for understanding the strength of electrostatic interactions. This approach is seen to provide excellent correlation between the electrostatic force and the binding energy between two partners in hydrogen-bonded complexes, as well as that between two ions in ion-pair complexes. Furthermore, we illustrate how the understanding of the binding allows for the rational design of new complexes where the association constant between the two partners can be increased or decreased, as desired, by several orders of magnitude. Hence, the current work showcases a general, simple and powerful method of understanding and exploiting long range secondary electrostatic interactions.